2021
DOI: 10.21037/atm-21-684
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-loaded thermo-sensitive hydrogel attenuates osteoarthritis by protecting cartilage and providing effective pain relief

Abstract: Background: We utilized the destabilization of medial meniscus (DMM)-induced mice to illustrate the osteoarthritis (OA) suppressing and pain-relieving effects of a novel prolonged-release intra-articular (IA)dexamethasone-loaded thermo-sensitive hydrogel (DLTH).Methods: The effects of temperature and pH on DLTH formation and in vitro DLTH release profile were assessed. C57BL/6J mice were randomly divided into three groups: Ctrl group Model group and DLTH group. The DLTH group received joint injections of 10 μL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…With chitosan-glycerin-borax as the carrier, Wang et al [107] used medial meniscus (DMM) instability in mice to illustrate the effect of a new intra-articular (IA)-loaded dexamethasone temperature-sensitive hydrogel (DLTH) on the inhibition and pain relief of osteoarthritis (OA). This in situ DLTH formed at 37 • C in the articular cavity.…”
Section: Osteoarthritismentioning
confidence: 99%
“…With chitosan-glycerin-borax as the carrier, Wang et al [107] used medial meniscus (DMM) instability in mice to illustrate the effect of a new intra-articular (IA)-loaded dexamethasone temperature-sensitive hydrogel (DLTH) on the inhibition and pain relief of osteoarthritis (OA). This in situ DLTH formed at 37 • C in the articular cavity.…”
Section: Osteoarthritismentioning
confidence: 99%
“…It can reduce the loss of collagen and proteoglycan in ECM, maintain ECM synthesis, and maintain the viability of chondrocytes. In addition, it is a key reagent for inducing chondrogenesis of MSCs in vitro ( García-Fernández et al, 2020 ; Wang et al, 2021e ; García-Couce et al, 2022 ). GlcN is a naturally occurring amino monosaccharide, widely used to reduce joint pain and repair cartilage ( Suo et al, 2020 ; Zhang et al, 2021c ).…”
Section: Materials Of Injectable Hydrogelsmentioning
confidence: 99%
“…Chondrogenic factors, 53 chondroitin sulfate nanoparticles, 54 and oligonucleotides 55 , 56 have been commonly loaded into hydrogel delivery systems for therapeutic studies. Some traditional medicines (such as celecoxib, 57 meloxicam, 58 dexamethasone, 59 and triamcinolone 60 loaded in hydrogel delivery systems not only provided improved long-term drug release, but also enhanced anti-inflammatory effect than the original formulations (See Table 2 for details).…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
“… [ 58 ] Chitosan Dexamethasone Slow release Thermal response In vivo Mice The cumulative release profiles of dexamethasone from hydrogels at 37 °C revealed a rapid release in the first 24 h and a sustained slow release for 7 days; In vivo studies showed that the drug-loaded hydrogels exerted a cartilage protective effect by reducing the expression of MMP-9, MMP-13, and ADAMTS-5, attenuated bone destruction in DMM-induced OA in mice, and improved synovitis and OA progression progress. [ 59 ] GEL-MAN Triamcinolone Slow release In vivo Mice In vitro, hydrogels can be continuously released for 24h under H 2 O 2 environment; In vivo experiments showed that the hydrogels group had a higher OARSI score, less inflammatory response, and less cartilage matrix degradation than triamcinolone acetonide alone. [ 60 ] Polyglucosamine/glucosamine carbonate ADMSCs Trestle In vivo Human Patients The initial WOMAC score of 58.6 ± 11.0 in the study group was reduced by 88% at 6 months (7.1 ± 9.2) and 95% at 24 months (2.9 ± 5.9); Separate biopsies performed at 12 months post-op in the study group also revealed type 2 collagen and hyaline-like cartilage in the regenerated tissue.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%